2020
DOI: 10.37077/25200860.2020.33.1.10
|View full text |Cite
|
Sign up to set email alerts
|

The Physico-Chemical Properties of Bovine and Buffalo Whey Proteins Milk by Using Ultrafiltration Membrane Technology

Abstract: The current study aims to prepare whey from bovine and buffalo fresh milk to make three types of cheese, namely: thermal, acidic and enzymatic. Afterward, whey proteins have been separated, then the concentration process of whey proteins has been conducted by using ultrafiltration membrane technology. Through the previous step, two products have been obtained; first, concentrated whey proteins which is called (Retentate), while the other is called (Permeate). Applying rotary evaporator, whey proteins are conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
1
Order By: Relevance
“…Among food products, milk and dairy products are useful for the immune system with their valuable proteins [32]. Epidemiological studies have shown that regular consumption of cow, mare and camel milk is characterized by a low prevalence of bacterial and viral infections in humans [33][34].…”
Section: қорытындыmentioning
confidence: 99%
See 1 more Smart Citation
“…Among food products, milk and dairy products are useful for the immune system with their valuable proteins [32]. Epidemiological studies have shown that regular consumption of cow, mare and camel milk is characterized by a low prevalence of bacterial and viral infections in humans [33][34].…”
Section: қорытындыmentioning
confidence: 99%
“…Тағам өнімдерінің ішінде сүт және сүт өнімдері құрамындағы бағалы ақуыздарымен иммундық жүйеге пайдалы [32]. Эпидемиологиялық зерттеулер сиыр, бие және түйе сүтін тұрақты тұтыну адамдарда бактериялық және вирустық инфекциялардың төмен таралуымен сипатталған [33][34].…”
unclassified
“…It is classified as a functional food because of its water-soluble components, including caseinates, whey proteins, polar lipids and milk fat globules membranes [1]. Milk is the basic material for making buttermilk, where it is one of the most important foodstuffs that contain many nutritional components, which are classified as GRAS, generally recognized as safe [2]. Butter milk is formed as a result of cracking the membrane of a milk fat granule and its connection with another pellet, releasing the oil and forming a network made of the accumulated fat globules, which leads to the phase reversal of the emulsion and the accumulation of butter granules and the separation of the milk mixture from it [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dairy products from livestock animals especially milk and its proteins are considered to be beneficial for human health and the immune system (Al-Hatim et al, 2020). The existing epidemiological studies showed that consumption of cow and camel's milk is correlated with the lower prevalence of bacterial and viral infections (Claeys et al, 2013).…”
Section: Introductionmentioning
confidence: 99%